(Auto) Biography, Memory and History (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The auto(biographical) narratives, in a diversity of genders (literary, testimonials, media, audiovisual), have an impor- tant place in the contemporary scene, not only as to the exemplary configuration of identities and subjectivities but also in regard to the construction of different meanings of public memory. From a theoretical exposition, where the re- lationship between biographical space, memory and history will run, I will discuss some conclusions of recent research on narratives of the recent past in Argentina, linked to the experience of the last military dictatorship (1976-1983), ar- ticulating testimonial records and auto(fictional) literature, film and visual arts, in the context of memory public poli- cies and current conflicts by its definition.
Keywords: Biographical space; Memory; History